The ethnoecology of Malay community to support management of functional food source areas in Belitung Regency, Indonesia - Prasaja, Dimas; Chikmawati, Tatik; Sulistijorini, Sulistijorini; Purwanto, Yohanes; Djuita, Nina Ratna (BRIN Publishing (Penerbit BRIN), 2025)
PRASAJA, D., CHIKMAWATI, T., SULISTIJORINI, S., PURWANTO, Y. & DJUITA, N. R. 2025. The ethnoecology of the Malay community to support the management of functional food source areas in Belitung Regency, Indone-sia. Reinwardtia 24(2): 199‒217. — The Malay community in Belitung Regency is rich in local knowledge about the management of the Belitung community landscape, which has been passed down from generation to generation. This local knowledge enables food production from its sources, but there is no information on the diversity and composi-tion of plants in the Belitung community's landscapes. This study aimed to analyze the diversity, composition, and conservation strategies of food plants in the Belitung community landscape. The study was conducted using the vege-tation analysis method, which created tiered square plots of various sizes. Plant conservation status is determined based on the ICS and the Important Value Index (IVI). The most common family found in all landscapes (rimba, bebak, kerangas bebak, kelekak, garden, homegarden) is Myrtaceae (21 species), except in rice fields, it is Poaceae, and in ume is Euphorbiaceae. Food plants are most found in homegarden landscapes (136 species included in 57 fami-lies). The cultivation and development of other potentials process must be carried out for plants with low/moderate IVI and high ICS, such as Ananas comosus, Arenga pinnata, and Cocos nucifera. Information from this research can sup-port efforts to diversify and provide food availability to realize food security based on local wisdom and local knowledge regarding the species diversity and the potential of local food plants in the Belitung Malay community. Traditional landscapes have an important role in providing sustainable food sources, as well as being a strong local identity, and providing economic contributions to the Belitung Malay community.